Association between radiographic anterior cruciate ligament tear and joint symptoms: Data from the osteoarthritis initiative. (26th February 2020) - Johnson, Victoria L.; Guermazi, Ali; Roemer, Frank W.; Hunter, David J.
Abstract: Introduction: Symptomatic osteoarthritis (OA) in the knee is defined as the presence of OA radiographic features in combination with knee symptoms. Pain has not been shown to correlate meaningfully to radiographic severity. We aimed to determine the relationship between a tear of the anterior cruciate ligament (ACL) with knee symptoms and radiographic OA. Methods: A within‐person, between‐knee cross‐sectional study of 37 participants from the Osteoarthritis Initiative (OAI) with a complete or partial ACL tear detected on magnetic resonance imaging in 1 knee (index knee) were included. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS) and radiographs of both knees, 1 with an ACL tear and one without (control knee) were scored for OA severity (Kellgren‐Lawrence Grading) and symptoms. A generalized estimating equation with linear regression was used to compare symptom scores within individuals as well as to radiographic severity. Results: Thirty‐seven individuals (40% female, average age = 60.7years, body mass index = 31.0 kg/m 2 ) reported no difference in knee symptoms (WOMAC pain odds ratio [OR] =1.92, 95%CI 0.699‐5.248, P = .21; KOOS symptoms OR = 2.12, 95%CI 0.740‐6.065, P = .09), stiffness (OR = 1.67, 95%CI 0.653‐5.583, P = .35) or functional disability (OR = 1 0.97, 95%CI 0.515‐7.508, P = .32) in the knee that exhibited an ACL tear compared to the control knee. Only knee function and disability (WOMAC Disability OR = 1.12, 95%CI 1.003‐1.249, P = .04) were associated with radiographic severity between index and control knees. Conclusion: Individuals did not report an increase in knee pain, stiffness or disability in their ACL‐deficient knee. Only disability was associated with worsening severity of radiographic OA in ACL‐deficient knees.